Management and planning of tools maintenance activities in a metalworking - Pires, C. R. (2016)
This paper presents an ongoing project in the metalworking section of a company that produces metal parts, responsible for the development and maintenance of production equipment tools. A tool is composed of several parts or punches whose failure causes production stoppage.The project's main goal is to make the planning and programming of activities to be performed by the section to be more efficient and reduce production downtime. In particular, it is intended that the maintenance work on the tools becomes preventive rather than corrective. The first step in the project realization was to design, develop and implement a computer application to collect the data needed to plan preventive maintenance actions, to monitor the work carried out by the technical area and to determine performance indicators.This paper presents the computer application and outlines the methodology to be adopted for setting the frequency of preventive replacement of parts, which consists on grouping of parts of the same tool to proceed with group replacements, thus limiting the number of production stoppages.The definition of part replacement frequency will allow planning and scheduling the activities of the metalworking, including the development of wear parts whose need is calculated based on the quantity of product units to be produced, the reliability of the part and the preventive replacements frequency. (C) 2016 The Authors. Published by Elsevier B.V.